PEMBELAJARAN BAHASA INDONESIA BERBASIS MEDIA NEARPOD DI MI THOLABIYAH MADIUN - Himmah, Ikrima Faiqotul; Yaqin, Zubad Nurul (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
The development of technology in the era of the industrial revolution 4.0 makes teachers have new challenges, especially in learning activities. This study aims to explain the use of learning media using digital technology media, namely the nearpod application or platform. This research uses descriptive qualitative. Data obtained from observations, field notes and interviews from one of the teachers at the Madrasah. The research subjects were 9 students at MI Tholabiyah. Meanwhile, the research object is the use of the nearpod application or platform in learning Indonesian with event material. The data source is obtained from learning conducted online by utilizing the nearpod platform. Based on the results and discussion that has been described, learning that is carried out using the nearpod application or platform can create a creative, innovative and fun learning atmosphere for elementary school students. Because the nearpod application has features that are needed by teachers and is easy to use.